Pengaruh Permainan Ludo Kimia Materi Pergeseran Kesetimbangan dan Faktor-Faktor yang Mempengaruhinya terhadap Hasil Belajar Peserta Didik Fase F SMA/MA - Lovia, Mutiara; Iswendi, Iswendi (ALSYS, 2025)
This study is motivated by the availability of the Ludo Kimia educational game for the topic of equilibrium shifts and their influencing factors, which has been proven to be valid and practical, yet its impact on student learning outcomes remains to be determined. The objective of this research is to examine the effect of using the Ludo Kimia game on the learning outcomes of Phase F high school students in the topic of equilibrium shifts. A quasi-experimental method was employed using a posttest-only control group design. The study population consisted of students from classes XI F1, XI F2, XI F3, XI F4, and XI F6 at SMAN 1 Batangkapas. The sample was selected through random sampling and included two classes: the experimental class (XI F2) and the control class (XI F1). Data were obtained from the posttest results and analyzed using a t-test. The analysis revealed that the average cognitive learning outcome score of the experimental class (75.16) was significantly higher than that of the control class (65.16), with a t-value of 3.34 > t-table value of 1.67 at a significance level of α = 0.05. Thus, it can be concluded that the use of the Ludo Kimia game in teaching the topic of equilibrium shifts and their influencing factors has a significant positive effect on improving the learning outcomes of Phase F students.